PENGARUH MODEL PEMBELAJARAN BU EMI TERHADAP PRESTASI MENULIS CERKAK SISWA KELAS IX DI SMP NEGERI 1 BAURENO KABUPATEN BOJONEGORO - Sudarwati, Emi; Mulyana, Mulyana (ITB AAS Indonesia Surakarta, 2024)
We know that writing skills in literature learning are skills that cannot be considered easy. Because this skill will certainly require a person's ability to be able to express ideas, ideas, thoughts and feelings so that they can become a work of art. Even other people can understand and feel the benefits of the work. So the learning outcomes that have been achieved by a school, whether high or low or good or bad, will really depend on the learning process. In particular, what learning experiences have been experienced and learned by the student. Because after all, experience is the best teacher. The author, as a Javanese language teacher, is fully aware that there are many students and students with different characteristics. Characteristics, abilities, knowledge, understanding, and so on in an effort to practice the material presented are certainly different. The aim of this research is to find out whether the BU EMI Model can improve the Cerkak writing achievement of class IX students at SMP Negeri 1 Baureno, Bojonegoro Regency. In this way, the Javanese language teaching and learning process is more effective and provides optimal results for students. Data resulting from the practical application of learning innovation at the first meeting, students seemed reluctant to write personal experiences into a Cerkak. Most likely this is because students generally feel they are not used to writing Cerkak and therefore find it difficult. That kind of thinking needs to be dismissed by using innovative learning models. Then the author tried to use the BU EMI Model. It turned out that class IX students became more enthusiastic. This can certainly increase students' grades in learning Cerkak Writing. In the end, this can also improve student achievement in learning Cerkak Writing. Cerkak is difficult. Such thinking needs to be pushed aside by using innovative models. Then the author uses this EMI BU Model. It turned out that class IX students became more enthusiastic. This certainly can increase student scores in Writing Cerkak. In the end it can also increase student achievement in learning Cerkak Writing.